The mediating effects of risk tolerance on fund performance. - Mahat, Fauziah; Md Nasir, Annuar; Ali, Noor Azman (Centre for Promoting Ideas (CPI), USA., 2010)
Risk tolerance in fund performance is a topic which is of enormous interest not only to researchers all over the world, but also to investors. Motivated by limited empirical studies on the effects of risk tolerance on fund performance in Malaysia and in response to reasonable gaps in the literature, the objective of this paper is to examine the mediating effect of individual fund manager risk tolerance(IFMRT) measured as level of confidence (LOC) and level of risk tolerance (LORT) as these mediate on the individual fund manager characteristics (IFMC) and fund performance (FP) relationship. The fund performance measures in this study use Sharpe (FPS), Treynor (FPT)m and Jensen (FPJ) ratios. The results indicate a weak linear correlation between individual fund manager characteristics and level of confidence, and also between individual fund manager characteristics and level of risk tolerance. Simultaneously, when the level of confidence and level of risk tolerance is added in the individual fund managers and fund performance relationship, it shows that the LORT variable acts as a mediator between IFMC and FP but LOC does not act as a mediator between IFMC and FP.